PROFIL UMUM AKNE VULGARIS PADA PELAJAR SEKOLAH MENENGAH ATAS NEGERI DENPASAR TIMUR - Ni Made Sruti Mahaswari Soethama; I Gusti Ayu Agung Elis Indira (Universitas Udayana, 2020)
Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous follicles which generally occurs in adolescence and can heal itself. Clinical features of acne vulgaris often polimorfi, consisting of various skin disorders such as blackheads, papules, pustules, nodes, and scarring that occurs due to abnormalities of the active, both hypotrophic and hypertrophic scarring. The prevalence of acne vulgaris that is equal to 96% and increases with age, which obtained the majority of students over 14 years old have experienced acne vulgaris. This study aims to determine the general profile of acne vulgaris with multiple characteristics at national senior high school students in East Denpasar. The research method is a descriptive cross-sectional study with a sample collection technique is cluster sampling. The sample in this study is the national high school students in East Denpasar District, namely SMA Negeri 1 Denpasar and SMA Negeri 3 Denpasar. This study used questionnaires and direct examination on the face and neck area to diagnose AV based on grading Indonesian Acne Expert Meeting (IAEM) in 2012. Data obtained through this research analyzed descriptively. The results showed that 244 of the 458 high school students suffer AV (53.3%). The data illustrates that the AV 121 from 244 students with AV suffered minor degrees (49.6%), 103 students suffered moderate AV (42.2%), and 20 students suffered severe degree AV (8.2%). Characteristics of respondents showed that 156 people were female (63.9%) and 88 were male (36.1%). Students with AV dominated by 16-year-old students (53.3%). Keywords: acne vulgaris, general profile, IAEM 2012